The Bourne Ultimatum - Ludlum, Robert (London Grafton Books, 1990)
At a small-town carnival, two men, each mysteriously summoned by telegram, witness a bizarre killing. The telegrams are signed (3z(BJason Bourne.(3y (BOnly they know Bourne$1 (Bs true identity and understand that the telegrams are really a message from Bourne$1 (Bs mortal enemy, Carlos, known also as the Jackal, the world$1 (Bs deadliest and most elusive terrorist. And furthermore, they know what the Jackal wants: a final confrontation with Bourne. Now David Webb, professor of Oriental studies, husband, and father, must do what he hoped never to do again$1 (Bassume the terrible identity of Jason Bourne. His plan is simple: to infiltrate the politically and economically omnipotent Medusan group and use himself as bait to lure the cunning Jackal into a deadly trap$1 (Ba trap from which only one of them will escape.s
Keywords: Bourne, Jason (Fictitious character) -- Carlos, The Jackal